Pengembangan Media Ular Tangga Terhadap Pembelajaran Matematika Materi Pecahan Sederhana Pada Siswa Sekolah Dasar - Ariyanto, Budi; Chamidah, Amalia; Suryandari, Savitri (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2020)
One of the problems in the teaching and learning process is the lack of use of instructional media. This resulted in learning mathematics becoming boring and not in demand by students. So here we need a media that can be used in learning mathematics, one of which is the snake ladder media that is developed for learning mathematics for simple fraction material in elementary school students. Development research uses the ADDIE model which has 5 stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evalution. But at the stage of the implementation of this study could not be applied because of the outbreak of COVID-19, so this study stopped at the stage of media expert validation and material validation as a measure of the feasibility of ladder snake media. The results of media validation were 90%, while the results of material validation 1 were 90% and material validation 2 were 92%. Then it can be concluded that the snake ladder media can be used for learning mathematics in simple fraction material in elementary school students.